INOVASI PEMBELAJARAN TEKNIK PASSING SEPAK BOLA MELALUI PJBL: DARI TEORI KE PRAKTIK LAPANGAN - Gressya, Iche; Annur, Fauziah; Syahfrizal, Arya; Akbar, Ariqah; Manalu, Nimrot (Universitas Negeri Medan, 2025)
This article examines the implementation of Project Based Learning (PJBL) as an innovative approach in the development of soccer passing skills. This research is motivated by the significant gap between the mastery of passing techniques in isolated training and application in real game situations in young Indonesian players. Conventional methods that rely on repetitive drills and one-way instructions have proven to be less effective in building players' contextual understanding and adaptive abilities. Through a qualitative-descriptive approach, this study analyzed the process of transforming the theoretical concept of PPA into field practice at three football schools in Central Java over a six-month period. The results showed that the implementation of PPA involving video analysis projects, collaborative training session design and thematic-based tournaments improved the passing accuracy (23.4%), decision making (31.7%) and tactical understanding (27.5%) of 13-15 year old players. Another important finding was the increase in intrinsic motivation and team collaboration as a positive impact of a more autonomous and contextualized learning approach. Key barriers to implementation included limited resources, coaches' resistance to methodological change, and challenges in the development of authentic assessments. The article concludes that PPA offers an effective pedagogical framework in bridging the theory-practice gap in learning.